A multiscale approach to simulating the conformational properties of unbound multi-C 2 H 2 zinc finger proteins - Liu, Lei; Wade, Rebecca C.; Heermann, Dieter W. (Proteins, 2015)
The conformational properties of unbound multi-Cys2His2 (mC2H2) zinc finger proteins, in which zinc finger domains are connected by flexible linkers, are studied by a multiscale approach. Three methods on different length scales are utilized. First, atomic detail molecular dynamics simulations of one zinc finger and its adjacent flexible linker confirmed that the zinc finger is more rigid than the flexible linker. Second, the end-to-end distance distributions of mC2H2 zinc finger proteins are computed using an efficient atomistic pivoting algorithm, which only takes excluded volume interactions into consideration. The end-to-end distance distribution gradually changes its profile, from left-tailed to right-tailed, as the number of zinc fingers increases. This is explained by using a worm-like chain model. For proteins of a few zinc fingers, an effective bending constraint favors an extended conformation. Only for proteins containing more than nine zinc fingers, is a somewhat compacted conformation preferred. Third, a mesoscale model is modified to study both the local and the global conformational properties of multi-C2H2 zinc finger proteins. Simulations of the CCCTC-binding factor (CTCF), an important mC2H2 zinc finger protein for genome spatial organization, are presented. Proteins 2015; 83:1604-1615. © 2015 Wiley Periodicals, Inc.